Child Protection Post the New Marriage Law: How Indonesian Religious Court Interpreting the Urgency in Child-age Marriage - Ilhami, Haniah; Nugraheni, Destri Budi; Wijayanta, Tata (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
The amendment of the Law of Marriage in 2019 introduces the new concept of Dispensation of Marriage by providing some additional provisions: the obligations to provide the urgency of marriage and the specific supporting evidence in proving the urgency. This article aims to examine the interpretations of judges in Religious Court on defining the urgency of child-age marriage and the implementation of the supporting evidence in cases of Dispensation of Marriage. Based on the identification, the author analyzes the main questions about the protection of children's rights on those interpretations. Based on the normative legal research that examines the Rulings of Religious Court on the case of Dispensation of Marriage, this article uses the Nonprobability Sampling techniques, specifically the purposive sampling which refers to certain criteria, the author finds the inconsistencies in the interpretation of the urgency of marriage and the implementation of providing the supporting evidence, which influenced by 2 (two) factors,  the Formal Regulation and the principle of judge’s independence. As a result, the author suggests detailed regulations regarding the supporting medical evidence, as well as the improvement of comprehensive and equal understanding for judges about the concept of child protection. Comparing to previous studies, this article shows its originality through a broader object study and comprehensive research analysis with more emphasis on juridical aspect, therefore that arguments and conclusions are built on a strong analytical foundation.